A Tragédia Grega em outro tempo e espaço: uma contribuição para o modelo didático do gênero - Santos, Luís César Sparsbrod (2014)
The objective of this research is to identify the defining characteristics of the genre tragedy adapted for the purpose of contributing to the construction of "teaching model" of this kind , from which propose activities that can enable the development of language skills for reading texts belonging to this genre . The teaching model is a descriptive object that shows the dimensions of a teachable genre. Its construction is only one step of a larger work on the teaching of genres and aims at elaborating didactic sequences , arranged according to the relationship between gender taken , his teachable characteristics and capabilities of proposed language ( ability to action, discursive , linguistic- discursive) expected to learners to develop . To achieve our goal, we seek to answer two questions : a) What are the defining characteristics of the genre adapted tragedy that can contribute to the construction of the teaching model? b) What language skills that can be developed with the teaching of reading this genre? This study initially presents the theoretical assumptions Interactionism sociodiscursivo ( Bronckart , 1999/2008 ), the assumptions of the same order that address the educational issues of teaching genres ( DOLZ , 1995; SCHNEUWLY , 1998; DOLZ & SCHNEUWLY , 2004) and studies in the field of literature and the dramatic text, the Theatre and the Greek Tragedies. (PASCOLATI, 2009; AGUIAR, 2009; ALMEIDA AND VIEIRA, 2007; KLEINMAN, 2008; ZANOTTO , 2005; 2008 among others ) . The corpus consists of tragedy adapted from Prometheus Bound . The analysis procedures focus on the conditions of production of these texts and their architecture involving the organization, the mechanisms of textualization and enunciative mechanisms. With the test results, we confirmed the importance of the production conditions for the constitution of the texts belonging to the tragedy genre, identify the defining characteristics of this genre and its contribution to development of the teaching model and suggest some activities for the development of a didactic sequence